Transformation plasticity in high strength, ductile ultrafine-grained FeMn alloy processed by heavy ausforming. (January 2022) - Lai, Qingquan; Yang, Huiqin; Wei, Yuntao; Zhou, Hao; Xiao, Lirong; Ying, Huiqiang; Lan, Si; You, Zesheng; Kou, Zongde; Feng, Tao; Lu, Qi; Jacques, Pascal; et al.
Highlights: Heavy ausforming leads to a fully austenitic ultrafine-grained FeMn microstructure. The ultrafine-grained FeMn alloy shows a large ductility, with no need of annealing. The high strain hardening capacity is due to the epsilon-martensitic transformation. Non-basal slip in the epsilon-martensite enables significant plastic co-deformation. The transformation-plasticity interaction is analyzed by a micromechanical model. Abstract: The mechanisms contributing to the excellent mechanical properties of the ultrafine-grained (UFG) Fe-23 wt.%Mn alloy processed by heavy ausforming are unraveled based on detailed characterization analysis and modelling. The UFG microstructure is fully austenitic after the heavy ausforming step involving a 90% rolling reduction; while the material quenched from the coarse-grained (CG) austenite consists of epsilon (ε)-martensite and austenite. The UFG Fe23Mn alloy shows a high strain-hardening capacity which leads to a much higher true uniform elongation (0.33) and true tensile strength (1330 MPa) than the CG counterpart (0.17 and 950 MPa, respectively). The high ductility of the heavily-ausformed microstructure with no subsequent annealing step contradicts the general trend of UFG alloys produced by severe plastic deformation. In addition, a ductile fracture mode with improved resistance to damage initiation in the UFG microstructure contrasts with the brittleness of the CG counterpart. Therefore, the UFG Fe23Mn alloy exhibits a high combination of strength, resistance to plastic localization and resistance to cracking. This superior mechanical performance is attributed to the gradual deformation-induced ε-martensitic transformation and to the large plastic co-deformation of the UFG ε-martensite, in which twinning is suppressed at the expense of the activation of non-basal slip. A mean-field micromechanical model is used to analyze the contribution of the phase transformation to plasticity, and to further rationalize the mechanical response of the UFG ε-martensite. This finding provides new insight into the effects of microstructural scale on the mechanical behavior of this class of transformation-induced plasticity (TRIP)-assisted alloys. Graphical abstract: Image, graphical abstract